Objetivos de Desarrollo Sostenible y buenas prácticas de economía solidaria en el Oriente Antioqueño - Alzate Cárdenas, Martha del Socorro (Universidad Católica Luis Amigó, 2021)
This book analyzes compliance with the application of the Sustainable Development Goals (SDGs), in coherence with cooperation practices typical of solidarity economy companies and organizations, in the Oriente Subregion, Department of Antioquia, Colombia.